Impact of the surface properties of lactic bacteria on the stability of emulsions - Mai Huong Ly (2005)
Bacteria have physicochemical surface properties which depend on the chemical composition of the cell surface. These characters proceed from several type of physicochemical interactions and are involved in attachment processes of microorganisms to surfaces. Thus they are of interest in several areas, as biomedicine, formation of biofilms and adhesion to apolar surfaces. Moreover, food matrix are complex heterogeneous media, which structure settles on interaction forces between molecules (van der Waals, electrostatic or structural forces…). When bacteria are present in a matrix, it is probable that their surface interacts with the other constituents. So far, few studies have mentioned this subject. In order to understand the involvement of cells surface properties in a food matrix, the effect of surface properties of lactic bacteria on the stability of model emulsions were studied. The results showed that the choice of a bacterium according to its surface properties may have a strong impact on the stability and on the behavior of an emulsion.